Memory, History, and Identity in Adalet Agaoglu's Dar Zamanlar Trilogy - Arikan, Seda; Aytan, Talat (Istanbul Univ, 2021)
Adalet Agaoglu's trilogy Dar Zamanlar [Narrow Times] addresses memory, history, and identity by depicting the development of its protagonist, Aysel, who begins her narrative as a little girl raised with Republican ideals and becomes an academician in the turbulent times of post-republican Turkish history. Evaluating the memory and identity formation of the individual and society in the context of the historical events of post-republic Turkey, this trilogy presents an essential critique of social and individual amnesia. The trilogy depicts how the individual and social memory should be revisited to construct the history and identity of individuals in particular as well as the society as a whole. At this point, Agaoglu's trilogy embodies the debates on the ethics of memory, a topic on which significant studies have been conducted since the twentieth century. The first novel of the trilogy, Olmeye Yatmak [Lying Down to Die], addresses the ethics of remembering against individual and social amnesia. The second novel, Bir Dugun Gecesi [A Wedding Night], reveals how individuals who prefer to forget past events would cause harm to themselves as well as to their society. Finally, the last novel of the trilogy, Hayir. [No.], defines forgetting as an act of insanity and proposes the birth of a New Human who could eliminate oblivion by revisiting history. In this respect, this study focuses on the moral side of forgetting and remembering in Agaoglu's Dar Zamanlar trilogy and aims to examine individual and social memory in terms of its relation to national history and identity by referring to the theories of the ethics of memory.
Keywords: Adalet Agaoglu; Dar Zamanlar trilogy; memory; history; identity